Association between beta‐blocker use and mortality/morbidity in older patients with heart failure with reduced ejection fraction. A propensity score‐matched analysis from the Swedish Heart Failure Registry. (23rd October 2019) - Stolfo, Davide; Uijl, Alicia; Benson, Lina; Schrage, Benedikt; Fudim, Marat; Asselbergs, Folkert W.; Koudstaal, Stefan; Sinagra, Gianfranco; Dahlström, Ulf; Rosano, Giuseppe; Savarese, Gianluigi
Abstract: Background: Beta‐blockers reduce mortality and morbidity in heart failure (HF) with reduced ejection fraction (HFrEF). However, patients older than 80 years are poorly represented in randomized controlled trials. We assessed the association between beta‐blocker use and outcomes in HFrEF patients aged ≥80 years. Methods and results: We included patients with an ejection fraction <40% and aged ≥80 years from the Swedish HF Registry. The association between beta‐blocker use, all‐cause mortality and cardiovascular (CV) mortality/HF hospitalization was assessed by Cox proportional hazard models in a 1:1 propensity score‐matched cohort. To assess consistency, the same analyses were performed in a positive control cohort with age <80 years. A negative control outcome analysis was run using hospitalization for cancer as endpoint. Of 6562 patients aged ≥80 years, 5640 (86%) received beta‐blockers. In the matched cohort including 1732 patients, beta‐blocker use was associated with a significant reduction in the risk of all‐cause mortality [hazard ratio (HR) 0.89, 95% confidence interval (CI) 0.79–0.99]. Reduction in CV mortality/HF hospitalization was not significant (HR 0.94, 95% CI 0.85–1.05) due to the lack of association with HF hospitalization, whereas CV death was significantly reduced. After adjustment rather than matching for the propensity score in the overall cohort, beta‐blocker use was associated with reduced risk of all outcomes. In patients aged <80 years, use of beta‐blockers was associated with reduced risk of all‐cause death (HR 0.79, 95% CI 0.68–0.92) and of the composite outcome (HR 0.88, 95% CI 0.77–0.99). Conclusions: In HFrEF patients ≥80 years of age, use of beta‐blockers was high and was associated with improved all‐cause and CV survival.